Silicon enhances plant resistance to Fusarium wilt by promoting antioxidant potential and photosynthetic capacity in cucumber (Cucumis sativus L.) - Sun, Shuangsheng; Yang, Zhengkun; Song, Zhiyu; Wang, Nannan; Guo, Ning; Niu, Jinghan; Liu, Airong; Bai, Bing; Ahammed, Golam Jalal; Chen, Shuangchen (Frontiers in Plant Science, 2022)
Fusarium wilt, caused by Fusarium oxysporum f. sp. cucumerinum (Fo), is a severe soil-borne disease affecting cucumber production worldwide, particularly under monocropping in greenhouses. Silicon (Si) plays an important role in improving the resistance of crops to Fusarium wilt, but the underlying mechanism is largely unclear. Here, an in vitro study showed that 3 mmol·L-1 Si had the best inhibitory effect on the mycelial growth of F. oxysporum in potato dextrose agar (PDA) culture for 7 days. Subsequently, the occurrence of cucumber wilt disease and its mechanisms were investigated upon treatments with exogenous silicon under soil culture. The plant height, stem diameter, root length and root activity under Si+Fo treatment increased significantly by 39.53%, 94.87%, 74.32% and 95.11% compared with Fo only. Importantly, the control efficiency of Si+Fo was 69.31% compared with that of Fo treatment. Compared with Fo, the activities of peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX) significantly increased by 148.92%, 26.47% and 58.54%, while the contents of H2O2, O2- and malondialdehyde (MDA) notably decreased by 21.67%, 59.67% and 38.701%, respectively in roots of cucumber plants treated with Si + Fo. Compared with Fo treatment, the net photosynthesis rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), the maximum RuBisCO carboxylation rates (Vcmax), maximum RuBP regeneration rates (Jmax) and the activities of ribulose-1,5-bisphosphate carboxylase (RuBisCO), fructose-1,6-bisphosphatase (FBPase) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and the expression of FBPA, TPI, SBPase and FBPase in Si+Fo treatment increased significantly. Furthermore, Si alleviated stomatal closure and enhanced endogenous silicon content compared with only Fo inoculation. The study results suggest that exogenous silicon application improves cucumber resistance to Fusarium wilt by stimulating the antioxidant system, photosynthetic capacity, and stomatal movement in cucumber leaves. This study brings new insights into the potential of Si application in boosting cucumber resistance against Fusarium wilt with a bright prospect for Si use in cucumber production under greenhouse conditions.